Reviews (Modern theology, 1990)
Book reviewed in this article: The Shadow of the Galilean: The quest of the historical Jesus in narrative form, by Gerd Theissen Being and Truth, Essays in Honour of John Macquarrie, edited by Alistair Kee and Eugene T. Long Atheist priest? Don Cupitt and Christianity, by Scott Cowdell